Devil's kitchen - Fox, Candice (Forge, Tor Publishing Group, 2024)
"This tight-knit, four-person unit has worked together to save countless lives and stop out of control fires before they cause major destruction. They've also stolen millions from banks, jewelry stores, and art galleries. Under the cover of saving the city, they've used their knowledge and specialist equipment to become the most successful heist crew on the East Coast. Andy Nearland is the newest member of the unit, and she's helping them prepare for their largest heist yet--New York's largest private storage facility, an expensive treasure trove for the rich and famous. She's also an undercover operative, and keeping her true motives hidden proves more and more dangerous as the day of the heist approaches"--